Lactic Acid Bacteria as Biocontrol Agents against Potato (Solanum tuberosum L.) Pathogens - Aleksandra Steglińska; Artur Kołtuniak; Ilona Motyl; Joanna Berłowska; Agata Czyżowska; Weronika Cieciura-Włoch; Małgorzata Okrasa; Dorota Kręgiel; Beata Gutarowska (Applied Sciences, 2022)
Biological control offers an alternative to chemical pesticides, which are inconsistent with the global trend of “going green”. Biological control includes various approaches, from natural predators to biologically produced molecules. This article focuses on the selection of lactic acid bacteria (LAB) as biological control agents against potato pathogens. The scope included evaluating the antimicrobial activity of 100 LAB strains against ten phytopatogens (Pectobacterium carotovorum, Streptomyces scabiei, Fusarium oxysporum, Fusarium sambucinum, Alternaria solani, Alternaria, tenuissima, Alternaria alternata, Phoma exigua, Rhizoctonia solani, Colletotrichum coccodes) by cross-streak plate method. HPLC determined the metabolic profiles for the most active LAB strains, and lactic acid, acetic acid, propionic acid and ethanol were found in the largest quantities. The strain Lactiplantibacillus plantarum KB2 LAB 03 was finally selected and cultured on supplemented acid whey. After the selection in laboratory tests, the strain KB2 LAB 03 was assessed in situ on seed potatoes against phytopathogens. The test showed a 40–90% reduction of eight potato pathogens infestation; only F. sambucinum and F. oxysporum were not inhibited at all. L. plantarum KB2 LAB 03 was proposed as the potential biocontrol agent for the potato protection against phytopathogens.